Gender Formation of Foster Children at Aisyiyah Female Orphanage of Tegal Municipality Based on Muhammadiyah Gender Ideology - Zaharani, Yuni; Malihah, Elly; Komariah, Siti (Komunitas, 2018)
Gender, together with all problems that it brings, becomes a discourse discussed in various countries, not excluding Indonesia. The Indonesian government through its policy keeps on creating gender equality and justice. The effort of government needs supports from all society elements, including orphanage. An orphanage needs to try to minimize and omit gender stereotype because the continuation of family informal socialization occurs here and it nurtures many children at the same times. The aim of this article is to analyse and describe children formation gender role at Putri Aisyiyah orphanage, Tegal based on Muhammadiyah gender ideology, whether it still preserves or has minimized and deleted gender stereotype. This research uses qualitative approach with the phenomenology design. The data is obtained by observation, interview, and documentation. The data analysis applies Miles and Huberman models. The formation of gender role at the orphanage is shown by the followings: the formation of gender role is done to form the female children as ideal women according to the orphanage. Ideal women according to the orphanage which is already similar to Muhammadiyah’s concept of gender, are those who can take parts in public without space leaving their obligations at home as wives and mothers. Independence, discipline, leadership are imposed to the children at the orphanage to support their roles in public. Feminism and domestic skills are educated to support their roles at homes.